The SAGE Encyclopedia of Corporate Reputation - CARROLL, Craig E. (Institutional Knowledge at Singapore Management University, 2016)
What creates corporate reputations and how should organizations respond? Corporate reputation is a growing research field in disciplines as diverse as communication, management, marketing, industrial and organizational psychology, and sociology. As a formal area of academic study, it is relatively young with roots in the 1980s and the emergence of specialized reputation rankings for industries, products/services, and performance dimensions and for regions. Such rankings resulted in competition between organizations and the alignment of organizational activities to qualify and improve standings in the rankings. In addition, today’s changing stakeholder expectations, the growth of advocacy, demand for more disclosures and greater transparency, and globalized, mediatized environments create new challenges, pitfalls, and opportunities for organizations. Successfully engaging, dealing with, and working through reputational challenges requires an understanding of options and tools for organizational decision-making and stakeholder engagement. The SAGE Encyclopedia of Corporate Reputation comprehensively overviews concepts and techniques for identifying, building, measuring, monitoring, evaluating, maintaining, valuing, living up to and/or changing corporate reputations.